Lingual Lymphangioma Ablation With High Power Diode Laser: A Case Report - Aires, Amanda Vieira; Kato, Camila Nazaré Alves de Oliveira; Silva, Leni Verônica de Oliveira; Andrade, Rodrigo Soares de; Júnior, HercÃlio Martelli; Ferreira, Marcus Vinicius Lucas; Mesquita, Ricardo Alves (Journal of Lasers in Medical Sciences, 2020)
Introduction: Lymphangioma is a rare vascular anomaly that affects the lymphatic vessels. Its etiology is not yet clear and it usually occurs in the head and neck region. This pathology is commonly diagnosed in childhood and there is no consensus about the most effective treatment of it. Case Report: We report a case of lymphangioma located on the dorsum of the tongue in a 9-year-old boy, with the clinical appearance of small transparent vesicles similar to “frog-eggs”. The diagnosis was defined according to the clinical aspect and ultrasound images. The treatment performed consisted of two sessions of ablation with a high-power diode laser. Conclusion: High-intensity diode laser ablation was a safe and effective tool for the treatment of this lesion in the tongue, which provided the patient with a faster, efficient transoperative period and a more comfortable postoperative period.